Development and validation of a novel detection method for Rickettsia rickettsii using a loop-mediated isothermal amplification assay - Carvajal-Gamez, Bertha I.; Olguín-Barrera, Aída; Tinoco-Gracia, Luis; Gordillo-Perez, Guadalupe; Dzul-Rosado, Karla; Aguilar-Tipacamú, Gabriela; Hidalgo-Ruiz, Mario; Mosqueda, Juan (Frontiers in Microbiology, 2024)
Introduction Rickettsia rickettsii is an obligate, intracellular pathogen and the causative agent of Rocky Mountain spotted fever (RMSF). RMSF is an important zoonotic disease due to its high fatal outcome in humans. The difficulty of clinical diagnosis due to the low sensitivity and specificity of current diagnostic methods are a principal setback. We reported the development of a new method for the detection of R. rickettsii in human and tick DNA samples using loop-mediated isothermal amplification (LAMP), as well as the validation of the LAMP test for R. rickettsii in field samples of infected ticks and humans, determining the diagnostic sensitivity and specificity, as well as the reproducibility of the test. Methods This technique uses hydroxy naphthol blue (HNB) as an indicator of the formation of magnesium pyrophosphate, a marker for the presence of DNA. Here, we used a putative R. rickettsii gene as a target for three pairs of primers that specifically amplify R. rickettsii DNA by hairpin-based isothermal amplification technique (LAMP). Results and discussion The sensitivity of the assay was 1.6–3 pg, which is 10 times more sensitive than PCR. To determine the diagnostics specificity and sensitivity, 103 human DNA samples and 30 tick DNA samples were evaluated. For the human samples, a sensitivity for HNB of 93%, a specificity of 70% and a k of 0.53 were obtained. For electrophoresis the sensitivity was 97% with a specificity of 58% and a k of 0.42. For tick samples, a sensitivity of 80% was obtained, a specificity of 93% for HNB and for electrophoresis the sensitivity and specificity were 87%. The k for both was 0.73. The degree of concordance between HNB and electrophoresis was 0.82 for humans and for ticks, it was 0.87. The result is obtained in shorter time, compared to a PCR protocol, and is visually interpreted by the color change. Therefore, this method could be a reliable tool for the early diagnosis of rickettsiosis.